WATER STEAM CONSUMPTION AND FEEDING SELECTION DEVICE CALCULATION INTO THE MIXING CHAMBER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Feed heat treatment analysis in stock breeding is given, the steam consumption results for heating feed mixtures in a continuous flow is determining with taking into account its losses when unloading the finished feed mixture.